2008
DOI: 10.1176/appi.ajp.2007.07030423
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic Density of Neighborhoods and Incidence of Psychotic Disorders Among Immigrants

Abstract: The incidence of psychotic disorders was elevated most significantly among immigrants living in neighborhoods where their own ethnic group comprised a small proportion of the population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
238
3
9

Year Published

2008
2008
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 302 publications
(274 citation statements)
references
References 33 publications
24
238
3
9
Order By: Relevance
“…In a more general sense, it is also possible that an underlying stress-factor associated with minority status could result in both the lower cognitive scores and the higher incidence rates in immigrants. Factors like stereotype threat (i.e., being at risk of confirming a negative stereotype about one's group) have been found to predict worse cognitive performance in immigrants [53], whereas other social stress factors such as discrimination [7,54,55] and urban ethnic density [56] appear to be related to the increased incidence of psychotic disorders in immigrants. Further research is warranted to expand and integrate existing cognitive [57] and ecological [58][59][60] models linking large cognitive deficits and increased incidence of psychosis in immigrant groups.…”
Section: Cannabis Usementioning
confidence: 99%
“…In a more general sense, it is also possible that an underlying stress-factor associated with minority status could result in both the lower cognitive scores and the higher incidence rates in immigrants. Factors like stereotype threat (i.e., being at risk of confirming a negative stereotype about one's group) have been found to predict worse cognitive performance in immigrants [53], whereas other social stress factors such as discrimination [7,54,55] and urban ethnic density [56] appear to be related to the increased incidence of psychotic disorders in immigrants. Further research is warranted to expand and integrate existing cognitive [57] and ecological [58][59][60] models linking large cognitive deficits and increased incidence of psychosis in immigrant groups.…”
Section: Cannabis Usementioning
confidence: 99%
“…As such it begins to illuminate those communities that are likely to face the largest inequalities in regard to the burden of severe mental illness. A body of international research (van Os et al 2000;Allardyce et al 2005;Veling et al 2008;Zammit et al 2010), including our own work in England (Kirkbride et al 2008(Kirkbride et al , 2012a, now suggests that social inequalities themselves are associated with increased rates of psychotic illness. Tools to identify and tackle regional inequalities in the social and economic determinants of mental health and well-being, as well as in inequalities in the allocation of resources within and beyond the mental health system, can serve as the evidence base upon which to found effective service delivery for the prevention and management of mental health disorders.…”
Section: Resultsmentioning
confidence: 99%
“…In The Hague and London, it was demonstrated that living in a neighborhood with a high proportion of residents of the own ethnic group is related to a lower risk for schizophrenia and low own-group ethnic density to a higher risk. 17,18 Das-Munshi et al 19 showed that potential markers of SD, such as discrimination, poor social support, and chronic strains, mediated the relationship between low owngroup ethnic density and presence of psychotic experiences. Zammit et al 14 showed that the ethnic density effect also operates at school level because it similarly applies to children with Swedish parents attending schools with a high proportion of foreign-born children.…”
Section: Evidence That Sd Explains Association With Migrationmentioning
confidence: 99%